STEAM and Islamic Education Integration in Madrasah: Cultivating Muslim Scientists from Early Education - Ihwanah, Al; Sirozi, Muhammad (Jurnal Cendekia Media Komunikasi Penelitian dan Pengembangan Pendidikan Islam, 2025)
This article aims to examine the integration of STEAM education (Science, Technology, Engineering, Arts, and Mathematics) with Islamic values at MI Al-Khoiriyah as an effort to foster scientific literacy among Muslim elementary students. A qualitative case study approach was employed, with data collected through classroom observations, in-depth interviews with teachers, and analysis of instructional documents. The findings reveal that project-based learning grounded in Islamic principles effectively enhances student engagement, strengthens understanding of scientific concepts, and promotes the development of critical and collaborative thinking skills. Integrating Islamic values into the learning process enables students to perceive science not merely as knowledge, but also as a means of strengthening faith and character. However, major challenges include the absence of a systematic, integrative curriculum and the limited capacity of teachers to implement interdisciplinary approaches. Therefore, this study recommends strong institutional support, continuous professional development programs for teachers, and developing a national curriculum that formally integrates STEAM with Islamic education. This integrative model is considered a strategic approach to shaping a generation of Muslim scientists who are intellectually competent and spiritually grounded from an early stage of education.